Gender-specific differences in central blood pressure and optimal target blood pressure based on the prediction of cardiovascular events - Kim, Min-Sik; Kim, Gee-Hee (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypertension (HBP) is a common disease among both men and women. Central blood pressure (CBP) is a method of evaluating aorta pressure that can assess the intrinsic BP of an individual patient that more closely correlates with cardiovascular disease (CVD) outcomes than peripheral BP parameters. We evaluated gender-specific differences in CBP and optimal target BP based on a composite outcome of CVD, heart failure (HF), and hypertensive complications in patients with HBP. Method: Patients were enrolled from June 2011 to December 2015 and were followed through December 2019. CBP was measured using radial tonometry. The primary endpoint was a composite outcome. Result: The median follow-up period for enrolled patients was 6.5 years. Out of a total of 2,115 patients with an average age of 57.9 ± 13.6 years, 266 patients (12.6%) had events of primary end points during the follow-up period. There was no difference in the lowest BP level between men and women in the incidence of CVD. Among the women (49.6%), 78.1% were postmenopausal. In a multivariable Cox proportional hazards model, CBP and systolic BP showed an increase in risk of 10% and 11%, respectively, with every 10 mmHg increase, and there was a similar trend of 12% and 13%, respectively, in postmenopausal women. However, PP showed an increase in risk of about 2% every 10 mmHg increase, but a tendency to increase risk by 19% in postmenopausal women. Conclusion: This study demonstrated that postmenopausal women will continue to show increased risk for CVD at BP higher than the optimal level. Conversely, there was no increase in CV risk due to menopause at BP values below the optimal level. Therefore, well-controlled BP is more important in postmenopausal women.